Relationship Between Individual Characteristics and Information Exposured with Halal Food Knowledge for Business Actors - Nadzirah Syilvia; Endah Budi Permana Putri (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2023)
Muslims will look for halal food products that are permitted to be consumed in their religion, not only in religion, but on a global scale there needs to be awareness of the importance of the quality of halal products by producers to sell products, so that a new perception regarding halal products arises. The aim of this research is to determine the relationship between individual characteristics and exposure to information with halal food knowledge among business actors. This type of research is observational research with a cross-sectional design. The sample in this study amounted to 40 respondents, sampling in this study used total sampling and measurement using a questionnaire. The data obtained were analyzed using the SPSS for Windows program and bivariate analysis was carried out using the Spearman correlation test type p value = <0.05. The research results show that the p value from Spearman statistical analysis shows the results of p value = 0.009 (age with knowledge), p value = 0.028 (gender with knowledge), p value = 0.046 (education with knowledge), p value = 0.337 (experience entrepreneurship with knowledge), p value = 0.050 (exposure to information with knowledge). Based on this analysis, it can be concluded that there is a relationship between age, gender, education and exposure to information and knowledge of halal food and there is no relationship between entrepreneurial experience and knowledge of halal food. It is hoped that there will be further research regarding halal food knowledge education using various other methods.